Política nacional de desarrollo y dependencia externa - Sunkel, Osvaldo (Estudios Internacionales, 1967)
For a national development policy to be effective, it must promote structural and institutional changes that are considered essential to meet specific social objectives. One of the fundamental objectives pursued by Economic Development Policy in many Latin American countries is overcoming situations of external dependency. It is therefore essential to examine the policies that are being promoted in the region and see if, in effect, they lead to this goal, or if on the contrary, they are moving towards greater external dependency. The result of this examination reveals the existence of contradictory trends, which is why some strategies and lines of action are outlined to reduce this dependency without affecting the acceleration of the economic growth rate.